Preparation method of composite modified asphalt

By chemically modifying waste lignin and preparing composite modified asphalt, the environmental protection problems of asphalt aging and anti-aging agents are solved, and the effect of extending the life of asphalt pavement and increasing the value of lignin is achieved.

CN119570272AActive Publication Date: 2025-03-07SOUTHEAST UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411673715.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing asphalt pavement aging under the action of complex environmental factors, resulting in changes in physical and chemical properties, increasing viscosity and brittleness, and reducing the service life of the pavement. At the same time, commonly used anti-aging modifiers have problems such as rheological performance impact, high cost and environmental pollution.

Method used

By dissolving the waste lignin with acidic lithium bromide solution, heating reaction, centrifugation, washing, suction filtration, vacuum drying and grinding, degraded lignin with increased phenolic hydroxyl content, and mixing it with quercetin, stabilizer and sodium xanthanate to prepare composite modified asphalt.

Benefits of technology

It improves the anti-aging and fatigue properties of asphalt, extends the service life of asphalt pavement, reduces oil resource consumption, and achieves the value-added utilization and environmental protection effects of lignin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a preparation method of composite modified asphalt, and particularly relates to the technical field of preparation of asphalt anti-aging agents. The preparation method comprises the following steps: mixing a lignin raw material with an acidic lithium bromide solution, and reacting under a heating condition; and after the reaction is finished, centrifuging, washing, carrying out suction filtration, carrying out vacuum drying and grinding to obtain the degraded lignin. The degraded lignin, quercetin, a stabilizer and sodium xanthate are used as anti-aging agents to be doped into asphalt, and the modified asphalt with high anti-aging performance is obtained. According to the invention, value-added utilization of lignin is realized, pollution of the lignin raw material to the environment is reduced, the use performance of asphalt is improved, and the consumption of non-renewable resources such as asphalt can be relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of asphalt anti-aging agents, in particular to a method for preparing composite modified asphalt. Background Art

[0002] Asphalt pavement is widely used due to its excellent performance. Compared with cement pavement, asphalt pavement has many advantages, such as comfortable driving, low noise, and convenient maintenance. In the construction of high-grade roads in my country, the proportion of asphalt pavement is as high as 90%. The design service life of asphalt pavement on highways is 15 to 20 years, but the actual service life is far less than this number. Most asphalt comes from the by-product of petroleum. The increase in demand for asphalt will further lead to the consumption of petroleum resources. Therefore, improving the life of asphalt pavement is an important direction of current road research.

[0003] The service life of asphalt pavement is closely related to asphalt aging. Under the influence of complex environmental factors (temperature, ultraviolet rays, oxygen, humidity), asphalt will age. During this process, its molecular weight increases and its chemical components are reorganized, resulting in changes in the physical and chemical properties of asphalt. This change increases the viscosity and brittleness of asphalt, and then it is prone to low-temperature and fatigue cracking under vehicle loads, which seriously reduces the service life of the pavement. Therefore, improving the anti-aging properties of asphalt is an urgent issue to be solved. The commonly used method is to add modifiers to improve the anti-aging properties of asphalt, including carbon black, industrial salts, nanomaterials, layered double hydroxides (LDH) and polymers. However, these materials have certain limitations in practical applications, including 1) affecting the rheological properties of asphalt materials; 2) high cost; 3) producing reagents that are harmful to the environment.

[0004] In contrast, lignin is a highly promising environmentally friendly anti-aging modifier due to its low cost, non-toxicity, renewable nature and similar molecular structure to asphalt. However, due to its heterogeneity and low reactivity, its anti-aging activity is limited, resulting in its limited application in asphalt antioxidants. In addition, lignin, as an industrial waste, is often used as a low-value fuel for heat and electricity, and less than 2% of lignin is used for value-added products other than fuel. This has a great impact on the environment. Therefore, in order to unleash the potential of lignin, processes that can physically and chemically modify lignin and improve its reactivity are urgently needed.

[0005] In summary, in order to save petroleum resources and scientifically solve the environmental pollution problem of waste lignin, using waste lignin for asphalt modification has important social and environmental value. At present, my country's research on lignin-modified asphalt is mostly focused on physical modification aspects such as experimental conditions (temperature, dosage, stirring intensity), and research on the chemical modification of asphalt by lignin is still insufficient.

[0006] The present application is different from the prior art as follows: Technical comparison with patent CN114539789A "A asphalt anti-aging agent and its preparation method and use method" Patent CN114539789A prepares an asphalt anti-aging agent by uniformly mixing untreated raw lignin material with quercetin, sodium xanthate, aromatic oil and stabilizer; while this patent pre-dissolves the raw lignin with acidic lithium bromide solution, obtains degraded lignin with increased phenolic hydroxyl content through heating reaction, centrifugation, washing, suction filtration, vacuum drying and grinding, and then uses the degraded lignin, quercetin, sodium xanthate and stabilizer to prepare composite modified asphalt. There is a fundamental difference between the two in the treatment of lignin, the raw material.

[0007] Patent CN114539789A obtains an asphalt anti-aging agent by pre-uniformly mixing lignin with quercetin, sodium xanthate, aromatic oil and stabilizer and performing shear treatment, and then mixes the anti-aging agent with asphalt in a specific ratio to prepare modified asphalt; this patent adopts a separate addition process, that is, degraded lignin, quercetin, stabilizer and sodium xanthate are added to the heated asphalt in proportion to prepare a composite modified asphalt. There are substantial differences between the two in the preparation methods of modified asphalt.

[0008] The raw materials used in the preparation of asphalt anti-aging agent in patent CN114539789A include lignin, quercetin, sodium xanthate, aromatic oil and stabilizer; while the raw materials used in the preparation of composite modified asphalt in this patent are degraded lignin, quercetin, stabilizer and sodium xanthate, and do not contain aromatic oil. There is a significant difference between the two in the raw materials for the preparation of modified asphalt.

[0009] Therefore, in order to solve the above problems, the present invention utilizes chemical modification of waste lignin, and then uses it to prepare composite modified asphalt to improve the anti-aging and anti-fatigue properties of asphalt and extend the service life of asphalt pavement. Summary of the invention

[0010] In order to solve the above technical problems, the present invention proposes a method for preparing a composite modified asphalt, which aims to start from the chemical depolymerization of lignin. The reaction conditions are simple and mild. The lignin is effectively degraded while preventing the self-polymerization of lignin, thereby increasing the reaction active sites of lignin. The composite modified asphalt prepared by degrading lignin has excellent anti-aging and anti-fatigue properties, and can partially replace petroleum asphalt.

[0011] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a composite modified asphalt comprises the following steps: (1) Lignin modification: Dissolve the sieved lignin in an acidic lithium bromide solution, heat and react in an oil bath, and after the reaction is completed, cool the reaction solution, centrifuge, wash, filter, vacuum dry and grind the reaction solution to obtain degraded lignin; (2) The degraded lignin obtained in step (1) is mixed with asphalt in a container, and the reaction container is placed in an insulation jacket for high-speed shearing treatment. During the shearing process, quercetin, a stabilizer and sodium xanthate are added in sequence. After the shearing is completed, a composite modified asphalt is obtained.

[0012] As a further improvement of the present invention, the mass concentration of the acidic lithium bromide solution in step (1) is 10-60%.

[0013] As a further improvement of the present invention, the reaction conditions of the lignin and acidic lithium bromide in step (1) are to react in an oil bath at 90-130° C. for 0.5-5 h.

[0014] As a further improvement of the present invention, the particle size of the lignin is 40-60 mesh.

[0015] As a further improvement of the present invention, the lignin includes hydrolyzed lignin, alkali lignin or organic lignin.

[0016] As a further improvement of the present invention, the acidic lithium bromide solution is prepared by adding HCl solution to a lithium bromide aqueous solution, the concentration of the lithium bromide solution is 10-60wt%, and the solution acid concentration is 0.5-2.4 mol / L, preferably 2.4 mol / L.

[0017] As a further improvement of the present invention, the mass volume ratio of lignin to the acidic lithium bromide solution is 1:10-15, preferably 1:10, g / mL.

[0018] As a further improvement of the present invention, during the centrifugation, washing, suction filtration and vacuum drying process, the filter cake is washed 3 to 4 times with deionized water, and the filter cake obtained after suction filtration is vacuum dried at 40 to 60°C.

[0019] As a further improvement of the present invention, the mass ratio of quercetin: stabilizer: sodium xanthate is 3~9:100:1~3:3~5:3~5.

[0020] As a further improvement of the present invention, the modified asphalt in step (2) is prepared as follows: The degraded lignin was mixed with asphalt and placed in a 150°C insulation jacket, the rotor of the shearing instrument was placed in the mixture, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and the shearing was stopped; quercetin was added, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and the shearing was stopped; stabilizer was added, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and the shearing was stopped; sodium xanthate was added, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and then the rotor speed was increased to 5000r / min, shearing for 40 minutes, and the shearing was stopped. After the shearing was completed, the mixed asphalt was cooled to room temperature to obtain the composite modified asphalt.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The composite modified asphalt prepared by the present invention has greatly improved anti-aging and anti-fatigue properties. After short-term aging, the carbonyl index of the composite modified asphalt is reduced by 30.5% to 47.4% compared with 70# matrix asphalt, and by 37.9% to 45.1% compared with unmodified lignin asphalt. The sulfoxide index is reduced by 18.2% to 31.4% compared with 70# matrix asphalt, and by 18.4% to 29.1% compared with unmodified lignin asphalt. After 50 hours of ultraviolet aging, the carbonyl index is reduced by 15.7% to 27.4% compared with 70# matrix asphalt, and by 13.1% to 25.2% compared with unmodified lignin asphalt. The sulfoxide index is reduced by 21.2% to 35.7% compared with 70# matrix asphalt, and by 18.2% to 33.2% compared with unmodified lignin asphalt. After 50 hours of ultraviolet aging, the fatigue life of the composite modified asphalt at a stress level of 2.5% is 6401 to 7109 times, and the fatigue life at a stress level of 5% is 429 to 491 times. Therefore, composite modified asphalt can be used instead of asphalt, which can not only realize the value-added application of lignin, but also improve the performance of road surface and reduce the consumption of petroleum resources. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below with specific embodiments:

[0023] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 2 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a vacuum drying oven at 40℃ to constant weight, and grind it after drying to obtain degraded lignin.

[0024] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 3g of quercetin, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of stabilizer, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of sodium xanthate, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, the mixed asphalt is cooled to room temperature to obtain a composite modified asphalt. Example

[0025] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 120℃ magnetic stirrer, turn on the magnetic stirrer, react for 2 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0026] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 2g of quercetin, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 4g of stabilizer, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 4g of sodium xanthate, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, the mixed asphalt is cooled to room temperature to obtain a composite modified asphalt. Example

[0027] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 3 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0028] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 1g of quercetin, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 3g of stabilizer, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 3g of sodium xanthate, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, cool the mixed asphalt to room temperature to obtain a composite modified asphalt. Example

[0029] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.0 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 2 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a vacuum drying oven at 40℃ to constant weight, and grind it after drying to obtain degraded lignin.

[0030] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 3g of quercetin, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of stabilizer, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of sodium xanthate, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, the mixed asphalt is cooled to room temperature to obtain a composite modified asphalt. Example

[0031] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 3 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0032] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 3g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 6g of quercetin, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of stabilizer, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of sodium xanthate, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, the mixed asphalt is cooled to room temperature to obtain a composite modified asphalt.

[0033] Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, place the container containing the asphalt in a 150℃ insulation jacket, place the rotor of the shearing instrument in the asphalt, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 20min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, cool the asphalt to room temperature.

[0034] Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of lignin and mix it with asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 20min, then increase the rotor speed to 5000r / min, shear for 40min, and stop shearing. After the shearing is completed, cool the mixed asphalt to room temperature to obtain lignin modified asphalt.

[0035] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 3 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0036] (2) Place 100 g of 70# matrix asphalt in a 150°C oven for 40 min, take 6 g of the degraded lignin obtained in step (1), mix it with the asphalt and place it in a 150°C insulation jacket, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000 r / min and keep it constant, shear for 20 min, then increase the rotor speed to 5000 r / min, shear for 40 min, and stop shearing. After the shearing is completed, cool the mixed asphalt to room temperature to obtain degraded lignin modified asphalt.

[0037] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 3 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0038] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of stabilizer, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of sodium xanthate, turn on the shear switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 45min, and stop shearing. After the shearing is completed, cool the mixed asphalt to room temperature to obtain a composite modified asphalt.

[0039] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 3 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0040] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of quercetin, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of sodium xanthate, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 45min, and stop shearing. After the shearing is completed, cool the mixed asphalt to room temperature to obtain a composite modified asphalt.

[0041] Dissolve 5g of lignin in a pressure bottle containing 50mL of acidic lithium bromide solution (lithium bromide concentration is 60wt%, hydrochloric acid concentration is 2.4 mol / L), seal the pressure bottle and place it in a 110℃ magnetic stirrer, turn on the magnetic stirrer, react for 3 hours, and then place the pressure bottle in ice water to cool and stop the reaction. Centrifuge the cooled reaction solution, wash, filter, and dry in a 40℃ vacuum drying oven to constant weight, and grind it after drying to obtain degraded lignin.

[0042] (2) Place 100g of 70# matrix asphalt in a 150℃ oven for 40 min, take 6g of the degraded lignin obtained in step (1) and mix it with the asphalt and place it in a 150℃ insulation cover, place the rotor of the shearing instrument in the mixture, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of quercetin, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, and stop shearing; add 5g of stabilizer, turn on the shearing switch, increase the rotor speed to 1000r / min and keep it constant, shear for 5min, then increase the rotor speed to 5000r / min, shear for 45min, and stop shearing. After the shearing is completed, cool the mixed asphalt to room temperature to obtain the composite modified asphalt.

[0043] The phenolic hydroxyl content of Examples 1-6 and Comparative Examples 1-6 and the carbonyl index and sulfoxide index of the modified asphalt under different aging conditions are shown in Table 1.

[0044] Table 1

[0045] By observing Example 1-4 and Comparative Example 2 through Table 1, it can be seen that compared with unmodified lignin, the phenolic hydroxyl content of degraded lignin is significantly increased, about 21.2%~35.4%, indicating that the use of the method of the present invention can effectively increase the phenolic hydroxyl content of lignin. Comparing Example 1-5 with Comparative Example 1-2, the carbonyl index and sulfoxide index of the composite modified asphalt under two aging conditions are less than 70# matrix asphalt, wherein the carbonyl index and sulfoxide index of Example 3 are the smallest. After short-term aging, the carbonyl index of Example 3 is reduced by 47.4% compared with 70# matrix asphalt, and the sulfoxide index is reduced by 31.4%. After 50 hours of UV aging, the carbonyl index of Example 3 is reduced by 27.4% compared with 70# matrix asphalt, and the sulfoxide index is reduced by 35.6%. The above data illustrate that the anti-aging performance of the composite modified asphalt is better than 70# matrix asphalt. Comparing Examples 1-5 and Comparative Examples 3-6, it can be seen that the modified asphalt to which degraded lignin, quercetin, stabilizer and sodium xanthate are added has the lowest carbonyl index and sulfoxide index. When any one of the aging agents is reduced, both indexes show an upward trend, especially Comparative Example 3, which shows the highest carbonyl index and sulfoxide index without the addition of quercetin, stabilizer and sodium xanthate, i.e., the anti-aging performance is poor. This shows that the addition of anti-aging in the composite modified asphalt of the present invention is crucial. The composite modified asphalt prepared by the present invention uses degraded lignin, quercetin, stabilizer and sodium xanthate at the same time, and has excellent anti-thermal oxidative aging effect, and also has a good anti-ultraviolet aging effect.

[0046] The fatigue life of Examples 1-6 and Comparative Examples 1-6 after 50 hours of UV aging is shown in Table 2.

[0047] Table 2

[0048] It can be seen from Table 2 that compared with 70# base asphalt, the fatigue resistance of modified asphalt at two stress levels is improved. Compared with the modified asphalt prepared with unmodified lignin, the fatigue life of the composite modified asphalt with degraded lignin is increased, especially in Example 3, which increases by 28.6% at 2.5% stress level and 35.6% at 5% stress level, indicating that degraded lignin can further improve the fatigue resistance of asphalt, thereby increasing the service life of asphalt. Similarly, the fatigue life of the composite asphalt in Examples 1-5 is higher than the fatigue life of the composite asphalt in Comparative Examples 3-6 lacking any anti-aging agent, which is 6401~7109 times at 2.5% stress level and 429~491 times at 5% stress level, which is necessary for explaining that the anti-aging agent in the present invention is necessary to significantly improve the fatigue resistance and is indispensable.

[0049] The present invention provides a method for preparing a composite modified asphalt, which realizes the value-added utilization of lignin. The manufactured composite modified asphalt can replace ordinary asphalt and has excellent anti-aging and anti-fatigue properties. In addition, the asphalt content in the composite modified lignin is lower than that in ordinary asphalt, and the amount of volatile organic matter is relatively reduced, which not only protects the environment, but also greatly reduces the harm to human health.

[0050] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.

Claims

1. A method for preparing a composite modified asphalt, characterized in that: The steps include: (1) Lignin modification: Dissolve the sieved lignin in an acidic lithium bromide solution, heat and react in an oil bath, and after the reaction is completed, cool the reaction solution, centrifuge, wash, filter, vacuum dry and grind the reaction solution to obtain degraded lignin; (2) The degraded lignin obtained in step (1) is mixed with asphalt in a container, and the reaction container is placed in an insulation jacket for high-speed shearing treatment. During the shearing process, quercetin, a stabilizer and sodium xanthate are added in sequence. After the shearing is completed, a composite modified asphalt is obtained.

2. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The mass concentration of the acidic lithium bromide solution in step (1) is 10-60%.

3. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The reaction conditions of the step (1) of lignin and acidic lithium bromide are as follows: the reaction conditions are 90-130° C. in an oil bath for 0.5-5 h.

4. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The particle size of the lignin is 40-60 meshes.

5. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The lignin includes hydrolyzed lignin, alkali lignin or organic lignin.

6. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The acidic lithium bromide solution is prepared by adding HCl solution to a lithium bromide aqueous solution, the concentration of the lithium bromide solution is 10-60wt%, and the acid concentration of the solution is 0.5-2.4 mol / L.

7. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The mass volume ratio of lignin to acidic lithium bromide solution is 1:10~15.

8. The method for preparing a composite modified asphalt according to claim 1, characterized in that: During the centrifugation, washing, suction filtration and vacuum drying process, the filter cake is washed with deionized water for 3 to 4 times, and the filter cake obtained after suction filtration is vacuum dried at 40 to 60°C.

9. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The mass ratio of lignin: asphalt: quercetin: stabilizer: sodium xanthate is 3-9:100:1-3:3-5:3-5.

10. The method for preparing a composite modified asphalt according to claim 1, characterized in that: The preparation of modified asphalt in step (2) is specifically as follows: The degraded lignin was mixed with asphalt and placed in a 150°C insulation jacket, the rotor of the shearing instrument was placed in the mixture, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and the shearing was stopped; quercetin was added, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and the shearing was stopped; stabilizer was added, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and the shearing was stopped; sodium xanthate was added, the shearing switch was turned on, the rotor speed was increased to 1000r / min and kept constant, shearing for 5 minutes, and then the rotor speed was increased to 5000r / min, shearing for 40 minutes, and the shearing was stopped. After the shearing was completed, the mixed asphalt was cooled to room temperature to obtain the composite modified asphalt.

Citation Information

Patent Citations

  • Method for dissolving lignin with lithium bromide solution

    CN111154117A

  • Asphalt anti-aging agent as well as preparation method and use method thereof

    CN114539789A

  • Lignin asphalt modifier as well as one-step preparation method and application thereof

    CN118956047A